Evaluation of Clinical Outcome of Subtrochanteric & Proximal Femur Fracture treated by Interlocking Intramedullary Nail with Side plate (Central Medical College Journal, 2022)
Fractures of the subtrochanteric region and proximal femur can be especially challenging to manage, and they warrant special consideration to obtain consistently satisfactory results. The subtrochanteric zone of the femur is generally considered to include the area extending 5 cm distally from the inferior border of the lesser trochanter, or the junction of the proximal one third and middle third of the femoral shaft. Fractures that have their major displacement in this area are considered subtrochanteric fractures despite the possibility that some of them may extend into the trochanteric area proximally or the distal femoral shaft. The management of fractures of the subtrochanteric region and proximal femur has always held a particular interest for orthopedic surgeons. Biomechanically, the subtrochanteric area of the proximal femur is an area of high stress concentration, which has led to high rates of implant failures in the treatment of these fractures. Current evidence suggested that interlocking intramedullary nail with side plate offer better outcome.Objectives: To evaluate the operative efficacy and clinical outcome of interlocking intramedullary nail with side plate in the treatment of subtrochanteric & proximal femur fracture.Methods: This prospective cross sectional study was conducted in Cumilla General Hospital and private Clinics, Cumilla, from April 2018 to November 2019 among the 62 cases of subtrochanteric femur fractures. Objective of this study was to find out a safe, effective management of fracture, early mobility of patient, functional joint motion and short stay in hospital. All patients were treated by interlocking intramedullary nail with side plate. Routine follow up was carried out and outcomes were assessed. Radiographic examination was used to evaluate callus formation and fracture healing in postoperative 1, 3, 6 and 12 months follow-up. Functional recovery was evaluated by Harris Hip Scoring (HHS) system.Result: In this study, the mean age was 49.3±8.5 years. Among 62 cases 52 cases (83.9%) were male and 10 cases (16.1%) were female. The male and female ratio was 5.2:1. Regarding the causes of injury, out of 62 patients 50 (81%) had a history of fall from height. In 12 (19%) cases, motor vehicle accident was the cause of fracture. Average time of healing was 18 weeks. According to Harris hip score findings, 46 cases were considered as excellent in functional recovery, 11 good, 4 fair and 1 poor. The proportion of the patients with excellent and good recovery was 91.8%.Conclusion: Study showed interlocking intramedullary nail with side plate provides better functional outcome with early mobility of patients, and fracture unites without joint stiffness and less complication.Central Medical College Journal Vol 5 No 2 Jul 2021 PP 88-93